흰쥐의 카드뮴 및 수은 중독시 유기 게르마늄의 Metallothionein형성에 관한 연구 - 이효민 (연세대학교 보건대학원, 1988)
[한글] 산업이 발달하면서 환경오염은 새로운 건강장애문제를 특히, 농약 및 유해중금속 등의 환경오염물질은 자연계 내의 잔유성이 매우 길고 그들의 생물축적 및 농축으로 인간에게까지 전달되어 만성적이며 고질적인 질병을 야기하고 있다. 유해 중금속 중 카드뮴 및 수은은 전기용품 및 화학용품등의 각종 산업용품에 많이 쓰이고 있는 중금속이며, 여러경로를 통하여 인체에 유입되어 각종 건강장애를 유발한다. 그러나, 유독성 카드뮴이나 수은이 생체에 유입되었을 때 일부는 뇨와 변 및 호흡을 통하여 대사되므로 독성물질의 체내 제거율이 흡수율을 초과할 경우, 생체에 유해작용을 일으키지 않는다. 일반적으로 카드뮴이나 수온은 간장 또는 신장에서 metallothionein을 형성하여 배설된다. 또한 각종 중금속들 간에는 생체 내에서, 특정 중금속과 공존할 때 여러가지 상호작용들로 인하여 그 유해성이 현저히 감소 또는 증가한다. 이에 본 연구는 흰 쥐를 대상으로 유기 게르마늄이 카드뮴 및 수은의 중독시 metallothionein형성에 미치는 영향을 관찰하기 위하여 시도되었다. 카드뮴(CdCl^^2) 및 수은(HgCl^^2)은 1/5LD^^50치의 용량을 매일 복강주사하였고, 유기 게르마늄 (GE-132)은 100mg/kg의 용량을 매일 위내투여하였다. 본 연구의 목적을 위하여 유기게르마늄을 카드뮴 및 수은과 병용투여하여 카드뮴 및 수은의 단독투여군과 성장변화, 해부검사, 혈청transaminase 활성도(SGOT 및 SGPT) 변화등을 비교관찰하고 신장 및 간장조직중의 중금속농도, matallothionein 농도 및 matallothi onein의 금속결합능등을 측정하였으며 그리고 각 조직의 병리학적 검경을 실시한 결과 다음과 같은 결론을 얻었다. 1. 카드윰 및 수은화합물의 투여로 흰쥐의 체중변화는 정상군에 비하여 저조한 증가 및 감소추세를 나타내었으며, 게르마늄 병용투여군에서도 역시 저조한 증가 및 감소현상을 나타내었다. 2. 해부검사 결과 카드뮴 및 수은 투여군에서 간장, 위장 및 폐등의 심한 장기유착과 간장 및 신장의 변색 그리고 간장 및 신장의 비대등이 뚜렷하게 관찰되었다. 그러나 카드뮴 및 게르마늄 투여군에서의 장기유착은 다른 투여군들에 비하여 다소 적게 관찰되었다. 3. 혈중GOT 및 GPT활성도 변화를 보면 모든 투여군에서 정상군에 비하여 유의하게 수치가 상승하였다. 카드뮴 단독투여군에 비하여 카드뮴 및 게르마늄 병용투여군에서 현저한 수치저하를 나타내었으나, 수은 단독투여군과 수은 및 게르마늄 병용투여군 간에는 유의한 차이가 없었다. 4. 카드뮴 또는 수은의 단독 그리고 이들과 게르마늄 병용투여후 간장과 신장조직중의 기간별 카드뮴, 수은 및 게르마늄의 농도를 측정하여 본 결과 게르마늄을 제외하고는 모든 투여군에서 기간이 경과함에 따라 축적농도가 증가하였다. 한편, 카드뮴 단독투여군과 카드뮴 및 게르마늄 병용투여군간의 기간별 축적농도 비교에서는 간장 및 신장조직 모두 유사한 카드뮴 축적농도를 나타내었다. 그러나, 수은단독투여군과 수은 및 게르마늄 병용투여군 간에는 간장에서는 서로 유사한 수은 축적농도를 나타내었지만 신장에서는 수은 단독투여군의 수치가 유의하게 높았다. 게르마늄은 모든 실험군에서 거의 검출되지 않았다. 5. 조직중 metallothionein 농도는 카드뮴 단독투여군에 비하여 카드뮴 및 게르마늄 병용투여군이 간장에서 훨씬 높은 수치를 내었으나 신장에서는 유사한 수치를 나타내었다. 따라서 게르마늄이 간장에서는 metallothionein형성을 촉진시켜 그 독성을 감소시킴을 알 수 있었다. 그러나 수은 단독투여군과 수은 및 게르마늄 병용투여군 간에는 간장과 신장에서 모두 유의한 차이를 나타내지 않았다. 6. 간장 및 신장조직중 metallothionein금속결합능을 구한 결과 정상군과 카드뮴 및 게르마늄 병용투여군의 간장을 제외하고는 모두 각 기간마다 수치의 변화를 나타내었다. 카드뮴 및 게르마늄 병용투여군의 간장에서는 전체적으로 거의 수치의 평형을 이루고있어 카드뮴의 체내축적농도와 metallothienein형성이 서로 비례함을 알 수 있었다. 7. 조직 병리학적 검경결과, 정상군을 제외한 모든 투여군에서 정도의 차이는 있었으나 간장조직 내에는 대체적으로 간소엽내에 변화가 있었으며 문맥의 변화는 실험후기에 다소 관찰될 뿐 그 정도가 미약하였다. 신장조직의 변화 또한 모든 투여군의 실험후기에 세관손상과 괴사등의 변화를 관찰할 수 있었으나 수은투여군을 제외하고는 그 정도가 미약하였다. 카드뮴 단독투여군에 비하여 카드뮴 및 게르마늄 병용투여군의 간장에서의 조직학적 병변이 훨씬 적게 나타났다. 즉, 간소엽내의 변화 및 문맥의 변화가 기간적으로 늦 게 나타났으며 그 변화도 적었다. 그러나 신장조직의 병변에는 별다른 차이가 없었다. 수은 단독투여군과 수은 및 게르마늄 병용투여군 간에는 간장과 신장조직 모두에서 뚜렷한 병변의 차이를 발견하지 못하였다. 이상의 결과로 보아 유기 게르마늄은 카드뮴과 병용투여시 간장에서 metallothionein 형성을 촉진시키므로 카드뮴의 독성을 감소시킨다. 그러나 수은과의 병용투여시는 수은의 독성을 감소시키지 못하였다. [영문] This study was initiated to investigate the effect of organic germanium on cadmium or mercury intoxication. The effect was determined by the metallothionein induction in liver and kidney. Male rats (Sprague-Dawley) were treated with CdCl^^2(2mg/kg), HgCl^^2(1mg/kg) and organic germanium (GE-132) (100mg/kg) in single or in combination via intraperitoneal infection or intragaatric administration every other days for 17 days. Experimental animals were sacrificed after 7, 12 and 17 days' treatment. The body weight, serum transaminase activities(SGOT, SGPT), concentration of metal and metallothionein, or metal-binding capacity of metallothionein in liver and kidney determined, and anatomical and pathomorphological observations were undertaken. The results were summarized as follows; 1. Rats exposed to cadmium or mercury showed significantly lower gain of body weight than the normal control group. Germainum treated rats showed the same value as the experimental groups in the weight gain. 2. All rats treated with metals showed remarkable abnormalities in their : internal organa in terms of adhesion of liver, lung and stomachs and discoloration aud enlargement of liver and kidney. Adhesion of liver, lung and stomach was slightly relived in rats of the combined treatment of GE-132 and CdCl^^2. 3. The combined treatment of GE-132 and CdCl^^2 decreased significantly the activities of serum transaminases to the single treatment of CdCl^^2. This indicated that GE-132 appreciably decreased toxicity of cadmium. However, the germainum treatment did not affect to activities of the transaminases induced by mercury. 4. The concentrations of metals (Cd and Hg) except Ge in the liver and kindney of rats increased with the time of treatment. The concentrations of cadmium in liver and kidney of rats treated with combined GE-132 and CdCl^^2 or with the single CdCl^^2 were not significantly different. Mercury concentration was significantly higher in kidney of rats with strangle treatment of HgCl^^2 than that of rats with the combined treatment of GE-132 and HgCl^^2, but the concentrations of mercury in liver were similar between them. 5. The concentrations of metallothionein in liver and kidney of rats increased with the time of treatment. The concentrations of metallothionein in liver of the combined treatment of GE-132 and CdCl^^2 were higher than that of single treatment of CdCl^^2, but values in kidney were similar between them. This indicates that GE-132 decreased toxicity of cadinium in liver by promoting metallothionein induction. There were no significant differences in metallothionein concentration in liver and kidney of rats between the combined treatment of GE-132 and HgCl^^2 and single treatment of HgCl^^2. 6. Metal-bidding capacity of metallothionein varied with each time intervals in liver and kidney of metal treated rats except the liver of the combined treatment of GE-132 and HgCl^^2. There were no variation in metal-binding capacity of metallothionein in liver of rats with the combined treatment of GE-132 and CdCl^^2. This explains the concentration of metallothionein in liver keeps abreast with the concentration of metals and this may explain a slight damage of liver tissue. 7. All treatment groups except control generally showed loubular necrosis and portal inflammation of liver tissues in the late period of experiment, but there were difference in degree of the damages between groups. Also, all treatment groups except control showed tubular damage and focal necrosis of kidney tissues in the late period of experiment, but the degree of damages were insignificant in the groups of combined treatment of GE-132 and CdCl^^2 and of single treatment of CdCl^^2. Pathologically less, changes in liver tissue were observed in rats of the combined treatment of GE-132 and CdCl^^2 than that in rats of single treatment of CdCl^^2; the damage of liver cell tissues, such as lobular necrosis and portal inflammation, was relieved and appeared more later, but there was no difference in damage of kidney tissue. However, no differences in damages of liver and kidney tissues were observed between the groups of combined treatment of GE-132 and HgCl^^2 and the single treatment of HgCl^^2. From the above results, organic germanium is considered to have some beneficial effect on the protection of liver from the cadmium intoxication.
환경관리학과/석사